ХИРУРГИЧЕСКОЕ ЛЕЧЕНИЕ РАЗРЫВА ПЕРЕДНЕЙ КРЕСТООБРАЗНОЙ СВЯЗКИ У ДЕТЕЙ: СРАВНЕНИЕ РАЗЛИЧНЫХ МЕТОДОВ - Щепин, Н А; Храмкова, А И; Токтобекова, Э Т; Щербаков, А И; Альмама, Я; Кешишян, Р А (FORCIPE, 2022)